2015
DOI: 10.1002/ccd.26117
|View full text |Cite
|
Sign up to set email alerts
|

Impact of comorbidities and gender on the use of coronary interventions in patients with high‐risk non‐ST‐segment elevation acute coronary syndrome

Abstract: Lower rates of coronary intervention in females persisted after adjusting for number of comorbidities which suggests that gender may bias decisions regarding referral for coronary intervention in high-risk NSTEACS independent of other factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
1
13
0
1
Order By: Relevance
“…In our study, men were found to be more exposed to chemotherapy at the end of life than women. This sex bias has been described before, both in end‐of‐life care settings and in other settings …”
Section: Discussionsupporting
confidence: 68%
“…In our study, men were found to be more exposed to chemotherapy at the end of life than women. This sex bias has been described before, both in end‐of‐life care settings and in other settings …”
Section: Discussionsupporting
confidence: 68%
“…African Americans and Asians were almost 30% less likely to receive CA. Teaching hospital status was associated with a higher use of CA compared to rural hospitals despite the expansion of angiography services in rural hospitals 16 .…”
Section: Discussionmentioning
confidence: 94%
“…Women, in most instances, are older when they exhibit their first manifestation of ACS, at a mean age of 71.8 years, compared to 65 years for men. 2 , 5 - 10 The older age of onset in women, when compared to men, is probably due to the protective role of estrogen circulation in the vascular endothelium. This hypothesis derives mainly from the observation that the incidence of AMI increases substantially in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%